Essential MATLAB for Engineers and Scientists. - Hahn, Brian (Elsevier Science, 2016)
Illustrating the essentials of MATLAB throughout, and featuring complete coverage of the software's windows and menus, this book provides a concise, balanced overview of MATLAB's functionality that facilitates independent learning, with coverage of both the fundamentals and applications. --